Capacity of Christian Educators in the Age of Community 5.0 - Marthen Mau (PT FORMOSA CENDEKIA GLOBAL, 2023)
The capacity of Christian educators is a skill or ability of Christian educators who apply true teaching in the midst of the 5.0 society that is being experienced or felt, so that it can be enjoyed by the general public. Society 5.0 as an era of society is centered on human interests in the world. The presence of society 5.0 aims to prosper the wider community. A qualitative type method with a library approach was used to obtain research results on the topic of the capacity of Christian educators in the era of society 5.0 which uses technology applications to build full comfort and welfare for all people, both physically and spiritually. The conclusion of this research is that Christian educators have the capacity to use application programs in the era of society 5.0 to lead, serve, teach, preach the Gospel, evangelize, have a missionary, dialogue, and apologetics, because technological developments in the era of society 5.0 are part of the primary need for the welfare of mankind